ANALISIS LEGAL STANDING PEMOHON DALAM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 90/PUU-XXI/2023 - Syaibani Ihza Ibrahim (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2024)
Testing of laws or judicial review at the Constitutional Court requires legal standing or legal position. Legal standing in the Constitutional Court Decision 90 caused problems because the applicant did not fulfill the requirements required to have legal standing in reviewing the law at the Constitutional Court. The method used is the normative juridical method, namely research that examines statutory regulations, principles, norms, scholarly doctrines, and decisions that have permanent legal force. The approaches used are the statutory approach and the case approach. The result is that the applicant in Decision 90 does not fulfill the required requirements because the applicant is not directly affected and/or causally affected by the enactment of Law Number 7 of 2017. Constitutional Court Decision No. 006/PUU-III/2006, namely the existence of constitutional rights granted by the 1945 Constitution, the applicant's constitutional rights are considered by the applicant to be disadvantaged by the law being reviewed, the loss is specific and actual, there is a cause and effect (causal verband), and there is a possibility By granting the request, constitutional losses will not or will not occur again.